A Literature Review on the Effectiveness of Project-Based Learning in English for Nursing strategies - I'in Noviana; Syaputra Dwi Santoso (Journal of Clinical Nursing Studies and Practice, 2025)
Proficiency in English is essential for nursing students to communicate effectively in various contexts, yet many face challenges with English for Specific Purposes (ESP) in nursing. Traditional teaching methods often fail to connect theoretical learning with real-world clinical applications. Project-Based Learning (PjBL) has emerged as an effective strategy to bridge this gap by allowing students to work on real-world projects that are directly relevant to their clinical practice. This literature review investigates the effectiveness of PjBL in enhancing English language proficiency and clinical competence in nursing education. A comprehensive search of studies from 2022 to 2025 from Scopus and Google Schoolar was conducted across relevant databases, focusing on keywords such as "Nursing Students," "PjBL," "ESP," "Clinical Competence," and "Student Engagement." Thirteen articles met the inclusion criteria, demonstrating that PjBL improves critical skills such as communication, problem-solving, and clinical readiness. Furthermore, the integration of AI in PjBL supports personalised learning, further engaging students. While PjBL has proven effective in bridging the theory-practice gap, challenges remain, including issues related to language proficiency and ICT integration. Further research is needed to explore the long-term effects of PjBL and its ability to address these challenges. Nursing education should continue implementing PjBL, with additional studies examining the role of AI in enhancing learning outcomes.